The Role of UMKM in Increasing Community Income in Sarirejo Village, Kaliwungu Sub-District - Siti Hikmatul Maula; Muh Ilham Shofiyan; Sofi Khoiriyah; Fidansa Rizki Aziz; Putri Adelya Insani; Hamimah Fitriyani; Arif Fadhilah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sarirejo Village is an area in Kaliwungu Sub-district that has shown significant progress in increasing community income through the development of Micro, Small and Medium Enterprises (MSMEs). The MSME industry in Sarirejo Village, especially the krupuk industry, has become one of the main sources of income for the local community. This article aims to describe the role of MSMEs in increasing community income and understand the potential and challenges faced, so that effective strategies can be formulated to improve community welfare and advance the local economy in Sarirejo Village. It is found that product innovation, entrepreneurship training, promotion and marketing, product packaging, and the implementation of Islamic business ethics have helped in the development of MSMEs in Sarirejo Village so that it will increase community income and welfare